Release of the lady beetle (Oenopia conglobata L.) to control the common pistachio psylla - Ozgen, Inanc; Mamay, Mehmet; Yanik, Ertan (Academic Press Inc Elsevier Science, 2022)
Common pistachio psylla, Agonoscena pistaciae Burckhardt & Lauterer (Hemiptera: Psyllidae), is a major pest of pistachio trees in Turkey, which can be difficult to control due to insecticide resistance. This study evaluated augmentative releases of larvae and adults of lady beetle, Oenopia conglobata L. (Coleoptera: Coccinellidae) for biological control of the psylla at densities of 25, 50, or 100 adults or larvae per tree in two pistachio orchards located in Turkey during 2016 and 2017. The pest population never reached the economic threshold in trees where 50 or 100 larvae or adults were released, whereas it exceeded the economic threshold in all other treatments (control and 25 larvae or adults release), locations-years except for Gaziantep in 2017. Higher release rates (100 larvae or adults per tree) reduced pest density by >50% on average, with efficacy ranging from 20% to 88%. The results indicate that augmentative releases of O. conglobata can result in additional generations of the predator in pistachio orchards. Although no differences were noted between releases of larval and adult stages of O. conglobata, release of large numbers of larvae in similar stages of development poses logistical challenges, rendering mass release of adults a more feasible approach. In conclusion, release of 100 adults per tree could be an effective biological control option for managing A. pistaciae in pistachio orchards.
Keywords: Oenopia conglobata; Larva and adult release; Efficacy; Pistachio orchards; Population suppression; Agonoscena pistaciae